Retail Evolution in Eastern European Countries: An Overview - Pentescu , Alma; Paștiu , Cosmin (KnE Social Sciences, 2020)
Retail has evolved a lot in the last years. Still, compared to more mature markets (such as US, UK, Germany, France, Sweden, the Netherlands), retail in Eastern European countries is less developed, with more balanced supply and demand. According to GfK’s report on European Retail in 2018, in 2017 there was a slight increase (+1.9 percent) in the purchasing power within the European Union (EU28) countries, Romania having the biggest increase (+7.8 percent) [1]. However, Romania’s low per capita purchasing power shows a gap in wealth levels across Europe. Huge differences between Western and Eastern Europe are visible also in terms of per capita values for retail space. Thus, the purpose of this descriptive research study is to analyze and compare how retail has evolved during recent years in Eastern European countries, with the help of several indicators. Data was collected from Eurostat and other industry reports. Results show that in EU28 countries the turnover in wholesale and retail trade has constantly grown (between 2011-2016), trend visible also in Bulgaria and North Macedonia. Per capita sales area increased too (between 2014-2017) in most Eastern European countries. This positive trend is visible also for retail turnover per m2 of sales area in all countries considered, although there are differences among them (with Bulgaria and Romania ranked the lowest and Cyprus and Greece the highest). Keywords: Retail, Eastern Europe, secondary data, indicators